The Contribution of Health Psychology to the Explanation of Health Behavior: An Integrative Analysis in Light of the Biopsychosocial Model and Its Implications for Social Health Work - Housni Kossai (Darul Yasin Al Sys, 2026)
In recent decades, the understanding of health and illness has undergone a profound epistemological shift, moving beyond purely biomedical explanations toward more integrative and multidimensional approaches. Within this context, Health Psychology has emerged as an interdisciplinary field concerned with examining the dynamic interactions between psychological, social, and biological factors in shaping health-related behaviors. This study aims to analyze the contribution of Health Psychology to understanding health behavior within the framework of the biopsychosocial model, while highlighting its implications for social work practice in healthcare settings. It also explores the role of psychosocial professionals in enhancing treatment adherence and promoting patients’ psychosocial adjustment through evidence-based interventions. The study adopts a descriptive-analytical approach based on a critical review of relevant literature, complemented by an illustrative case study to demonstrate the complex interplay of determinants influencing health behavior. The findings indicate that health behaviors are shaped by the interaction of psychological variables (e.g., health perceptions and self-efficacy), social determinants (e.g., social support and cultural context), and biological factors, thereby underscoring the limitations of reductionist biomedical models. The study concludes that integrating Health Psychology principles into social work practice enhances the effectiveness of healthcare, improves quality of life, and strengthens interdisciplinary collaboration within healthcare institutions. This study contributes to the existing literature by providing an integrative analytical framework linking Health Psychology with social work practice in healthcare settings, particularly within under-researched Arab contexts. It also offers a conceptual bridge between theory and practice through the application of the biopsychosocial model in a real-world illustrative case.